Improvement in clinical signs and cellular immunity of dogs with visceral leishmaniasis using the immunomodulator P-MAPA - Santiago, Maria Emília B. [UNESP]; Neto, Luiz Silveira [UNESP]; Alexandre, Eduardo Costa [UNESP]; Munari, Danísio Prado [UNESP]; Andrade, Mariana Macedo C. [UNESP]; Somenzari, Marcos Arruda [UNESP]; Ciarlini, Paulo Cesar [UNESP]; Lima, Valéria Marçal Felix de [UNESP] (Elsevier, 2013)
This study investigated the immunotherapeutic potential of the protein aggregate magnesium-ammonium phospholinoleate-palmitoleate anhydride immuno-modulator (P-MAPA) on canine visceral leishmaniasis. Twenty mongrel dogs presenting clinical symptoms compatible with leishmaniasis and diagnosis confirmed by the detection of anti-leishmania antibodies were studied. Ten dogs received 15 doses of the immunomodulator (2.0mg/kg) intramuscularly, and 10 received saline as a placebo. Skin and peripheral blood samples were collected following administration of the immunomodulator. The groups were followed to observe for clinical signals of remission; parasite load in the skin biopsies using real-time PCR, the cytokines IL-2, IL-10 and IFN-γ in the supernatant of peripheral blood mononuclear cells stimulated in vitro with either total promastigote antigen or phytohemagglutinin measured by capture ELISA, and changes in CD4+ and CD8+ T cell subpopulations evaluated by flow cytometry. Comparison between the groups showed that treatment with the immunomodulator promoted improvement in clinical signs and a significant reduction in parasite load in the skin. In peripheral blood mononuclear cell cultures, supernatants showed a decrease in IL-10 levels and an increase in IL-2 and IFN-γ. An increase in CD8+ T cells was observed in peripheral blood. In addition, the in vitro leishmanicidal action of P-MAPA was investigated using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and no leishmanicidal activity was detected. These findings suggest that P-MAPA has potential as an immunotherapeutic drug in canine visceral leishmaniasis, since it assists in reestablishing partial immunocompetence of infected dogs. © 2013 Elsevier B.V.
Keywords: CD4+ T; CD8+ T; Leishmania; P-MAPA; T lymphocytes; 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; antileishmanial agent; gamma interferon; interleukin 10; interleukin 2; Leishmania antibody; phytohemagglutinin; placebo; protein aggregate magnesium ammonium phospholinoleate palmitoleate anhydride; protozoal antigen; protozoal protein; protozoon antibody; unclassified drug; antibody; antigen; blood; canid; drug; immunity; leishmaniasis; parasite; symptom; animal tissue; antibody detection; blood sampling; CD4+ T lymphocyte; CD8+ T lymphocyte; cell culture; cell stimulation; cellular immunity; clinical feature; controlled study; cytokine production; dog disease; enzyme linked immunosorbent assay; flow cytometry; immunocompetence; immunomodulation; immunostimulation; immunotherapy; in vitro study; mononuclear cell; nonhuman; parasite load; promastigote; real time polymerase chain reaction; remission; skin biopsy; symptomatology; T lymphocyte subpopulation; visceral leishmaniasis; Canis familiaris